2022
DOI: 10.35812/cellulosechemtechnol.2022.56.86
|View full text |Cite
|
Sign up to set email alerts
|

EXTRACTION OPTIMIZATION OF A SUPERPOROUS POLYSACCHARIDE-BASED MUCILAGE FROM Salvia spinosa L.

Abstract: Herein, we optimized eco-friendly extraction parameters to get the maximum yield of a novel polysaccharide-based mucilage (SSH) from seeds of Salvia spinosa. The dependency of the extraction yield of SSH on the pH of the extraction medium (pH 6-8), extraction temperature (25-75 °C), seed/water ratio (1:10-1:40 w/v), and seed–water contact time (1-4 h) was evaluated using response surface methodology–Box Behnken design (RSM–BBD). A second-order polynomial equation provided the best fit to the studied response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…However, there may be a chance of polysaccharide degradation after 80 • C; therefore, the yield of AVM was found to decrease after 80 • C. A similar trend was observed by Nazir et al [20] for the optimization of hydrogel extraction conditions from Ocimum basilicum seeds. This trend may corroborate the thermal degradation of the polysaccharides present in the hydrogel upon the increasing temperature up to an optimum level and led to a decrease in the yield of hydrogels [16].…”
Section: Temperaturesupporting
confidence: 66%
See 3 more Smart Citations
“…However, there may be a chance of polysaccharide degradation after 80 • C; therefore, the yield of AVM was found to decrease after 80 • C. A similar trend was observed by Nazir et al [20] for the optimization of hydrogel extraction conditions from Ocimum basilicum seeds. This trend may corroborate the thermal degradation of the polysaccharides present in the hydrogel upon the increasing temperature up to an optimum level and led to a decrease in the yield of hydrogels [16].…”
Section: Temperaturesupporting
confidence: 66%
“…Moreover, 4.0 is the normal value of ADP. If the value of ADP is >4.0, then the model is desirable, and vice versa [16]. In this present study, the ADP value was found to be 22.59, which is greater than the normal value (Table 2).…”
Section: S/w Timecontrasting
confidence: 44%
See 2 more Smart Citations